BIOACTIVE COMPOUNDS AND ANTIOXIDANT CAPACITY FROM FIVE TYPES OF SEEDLINGS - Florina Maria Copaciu (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2016)
After germination process, the green seedlings accumulate important quantities of bioactive compounds such as: enzymes, vitamins, minerals, chlorophylls and nutrients. The current study presents a comparison between different bioactive compounds and their antioxidant capacity, after the seedling germination and growth of five seeds (arugula, lentil, wheat, beans and mustard) both on soil, in a pot (natural system), and directly on cotton wool soaked, in water (artificial system). In this study the carotenoids content and the antioxidant capacity were analysed. The data of the present study showed that the highest amount of zeaxanthin and β - carotene was found in cultivars of wheat grown in natural system, while the highest antioxidant activity was found in cultivars of wheat, lentils and beans, though in this case with no statistical differences between the systems. The results show statistical differences between the values of bioactive compounds in the five types of seedlings but also in the values obtained for the same seedlings in different systems. The best cultivars for improving the nutritional quality for human consumption are wheat seedlings followed by lentil ones.